Non-dimensional study on the start-up process of a centrifugal pump and its related pipe system. Issue 1 (January 2021) - Meng, L; Wang, W P; Liao, C L; Zhao, L C; He, L; Zhang, C Y
Abstract: Hydraulic transient processes sometimes bring with it violent or dramatic unsteady phenomenon, which would interfere the normal operation or even damage the system. The start-up of a centrifugal pump with cavitation can lead to serious transient phenomenon. One dimensional calculation (Method of characteristics) was widely used to solve transient problems, but its drawback is lacking of details for the flow characteristics inside the pump, 3D simulation for transient process simulation needs huge computer resources. A simulation method that coupled MOC and 3D simulation (CFD) was frequently used for solving complex transient problems in these years. The results of the coupling simulation are usually complex when cavitation happens and disappears quickly during the short start-up period, a simplified method to describe the process is necessary. A centrifugal pump and its related system were simulated with a coupling method. Dimensionless mass flow rate, head and cavitation conditions of the pump was used to analyse the start-up process. It was proved that the non-dimensional study method can make the whole process more intuitive and easier to understand.